(untitled) (ex æquo, 2023)
Gender, Sexuality and Online Activism: An intersectional look at the role of civic engagement by portuguese youth This paper results from an exploratory work about how youngsters living in Portugal use and think about new media in the process of constructing their subjectivity when it comes to engaging in online activism in the area of intimate citizenship. We employ intersectionality here to understand how this activity is interpreted or morally valued by people in different intersecting social positions. From eleven interviews conducted with youngsters residing in Portugal, analyzed through Foucauldian Discourse Analysis, we seek to understand how these people comprehend the potentialities and problems that come from using new media, considering the intersections between citizenship, gender and sexuality